Posttransplant Intramuscular Injection of PLX-R18 Mesenchymal-Like Adherent Stromal Cells Improves Human Hematopoietic Engraftment in A Murine Transplant Model - Metheny, Leland; Eid, Saada; Lingas, Karen; Ofir, Racheli; Pinzur, Lena; Meyerson, Howard; Lazarus, Hillard M.; Huang, Alex Y. (Frontiers in Medicine, 2018)
Late term complications of hematopoietic cell transplantation (HCT) are numerous and include incomplete engraftment. One possible mechanism of incomplete engraftment after HCT is cytokine-mediated suppression or dysfunction of the bone marrow microenvironment. Mesenchymal stromal cells (MSC) elaborate cytokines that nurture or stimulate the marrow microenvironment by several mechanisms. We hypothesize that the administration of exogenous MSCs may modulate the bone marrow milieu and improve peripheral blood count recovery in the setting of incomplete engraftment. In the current study, we demonstrated that post-transplant intramuscular administration of human placental derived mesenchymal-like adherent stromal cells (PLX-R18) harvested from a 3-dimensional in vitro culture system improved post-transplant engraftment of human immune compartment in an immune-deficient murine transplantation model. As measured by the percentage of CD45+ cell recovery, we observed improvement in the peripheral blood counts at weeks 6 (8.4% vs. 24.1%, p <0.001) and 8 (7.3% vs. 13.1%, p<0.05) and in the bone marrow at week 8 (28% vs. 40.0%, p <0.01) in the PLX-R18 cohort. As measured by percentage of CD19+ cell recovery, there was improvement at weeks 6 (12.6% vs. 3.8%) and 8 (10.1% vs. 4.1%). These results suggest that PLX-R18 may have a therapeutic role in improving incomplete engraftment after HCT.